Amyotrophic Lateral Sclerosis Survival Associates With Neutrophils in a Sex-specific Manner. Issue 2 (2nd March 2021) - Murdock, Benjamin J.; Goutman, Stephen A.; Boss, Jonathan; Kim, Sehee; Feldman, Eva L.
Abstract : Objective: To determine whether neutrophils contribute to amyotrophic lateral sclerosis (ALS) progression, we tested the association of baseline neutrophil count on ALS survival, whether the effect was sex specific, and whether neutrophils accumulate in the spinal cord. Methods: A prospective cohort study was conducted between June 22, 2011, and October 30, 2019. Blood leukocytes were isolated from ALS participants and neutrophil levels assessed by flow cytometry. Participant survival outcomes were analyzed by groups (<2 × 10 6, 2–4 × 10 6, and >4 × 10 6 neutrophils/mL) with adjustments for relevant ALS covariates and by sex. Neutrophil levels were assessed from CNS tissue from a subset of participants. Results: A total of 269 participants with ALS within 2 years of an ALS diagnosis were included. Participants with baseline neutrophil counts over 4 × 10 6 /mL had a 2.1 times higher mortality rate than those with a neutrophil count lower than 2 × 10 6 /mL (95% CI: 1.3–3.5, p = 0.004) when adjusting for age, sex, and other covariates. This effect was more pronounced in females, with a hazard ratio of 3.8 (95% CI: 1.8–8.2, p = 0.001) in the >4 × 10 6 /mL vs <2 × 10 6 /mL group. Furthermore, ALS participants (n = 8) had increased neutrophils in cervical ( p = 0.049) and thoracic ( p = 0.022) spinal cord segments compared with control participants (n = 8). Conclusions: Higher neutrophil counts early in ALS associate with a shorter survival in female participants. Furthermore, neutrophils accumulate in ALS spinal cord supporting a pathophysiologic correlate. These data justify the consideration of immunity and sex for personalized therapeutic development in ALS. Classification of Evidence: This study provides Class III evidence that in female participants with ALS, higher baseline neutrophil counts are associated with shorter survival.